Narco Analysis Test - A Boon to Criminal Investigation Process - A Critical Analysis - A.Vedha Valli , K.Sofiya , (International Journal of Advanced Science and Technology, 2020)
The primary intention behind using of the narco analysis test is the extraction of information from an uncooperative individual. Narco analysis was earlier used as a   therapy to treat psychological is associated with battles. Today, it is accepted test having legal, clinical and ethical consequences.  This article attempts to critically investigate whether it a boom to the criminal investigation process and the acceptance of the same by citing various legal issues, it relevance to the Indian Constitution which guarantee the right to privacy and with reference to the Indian Evidence Act deals with the right against self-incrimination and the human rights act.